Surgical treatment strategies for gastroesophageal reflux after laparoscopic sleeve gastrectomy - Liu, Genzheng; Wang, Pengpeng; Ran, Shuman; Xue, Xiaobin; Meng, Hua (Frontiers in Endocrinology, 2024)
Bariatric surgery has emerged as an effective therapeutic approach for combating obesity. As the most commonly performed bariatric surgery, laparoscopic sleeve gastrectomy (LSG) has a long-term and effective outcome in weight reduction.However, studies have reported an increased incidence of gastroesophageal reflux disease (GERD) among patients after LSG. For those who fail to respond to conventional oral acid-suppressing medication, surgical intervention comes into consideration.The most commonly performed revisional surgery for sleeve gastrectomy is the Rouxen-Y gastric bypass, which can effectively alleviate the symptoms of reflux in patients and also continues to promote weight loss in patients who have not achieved satisfactory results or have experienced weight regain. In addition to this established procedure, innovative techniques such as laparoscopic magnetic sphincter augmentation (MSA) are being explored. MSA is less invasive, has good reflux treatment outcomes, and its safety and efficacy are supported by the literature, making it a promising tool for the future treatment of gastroesophageal reflux. This article also explores the role of endoscopic interventions for GERD treatment of post-sleeve gastrectomy patients. Although these methods have shown some therapeutic effect, their efficacy still requires further study due to a lack of support from more clinical data.For patients with preoperative hiatal hernia or gastroesophageal reflux symptoms, some experts now consider performing LSG combined with hiatal hernia repair or fundoplication to alleviate or prevent postoperative reflux symptoms. Both of these surgical approaches have demonstrated favorable outcomes; however, the addition of fundoplication requires further investigation regarding its long-term effects and potential postoperative complications. This article gathers and examines the current laparoscopic and endoscopic treatments for refractory gastroesophageal reflux following LSG, as well as the concurrent treatment of LSG in patients with preoperative gastroesophageal reflux or hiatal hernia.